Neuroanatomical localization of nitric oxide synthase (nNOS) in the central nervous system of carp, Labeo rohita during post‐embryonic development. Issue 46 (2nd July 2015) - Biswas, Saikat P.; Jadhao, Arun G.; Bhoyar, Rahul C.; Palande, Nikhil V.; Sinh, Dharmendra P.
Abstract: Nitric oxide (NO) is a chemically diffusible molecular messenger playing various roles in both vertebrates and invertebrates. Nitric oxide synthase (NOS) is the key enzyme in synthesis of NO. The neuroanatomical distribution pattern of neuronal nitric oxide synthase (nNOS) was studied and developing stages of Labeo rohita such as hatchlings (10–15 mm), frys (15–35 mm), semi‐fingerlings (35–65 mm), fingerlings (65–100 mm) and adults (350–370 mm) were used. In the telencephalon, nitrergic cells were observed in both pallial and subpallial regions along with entopeduncular nucleus suggesting the involvement of NO in the control of sensory functions throughout the development. In the diencephalon, nNOS positive neurons were localized in the nucleus preopticus periventricularis and preopticus parvocellularis throughout development while nucleus preopticus magnocellularis was found immunopositive only in adult specimens who suggest the involvement of NO in the hormonal regulation. nNOS immunoreaction was also noted in suprachaismatic nucleus, habenula, lateral tuberal nucleus, paraventricular organ and anterior division of preglomerular nucleus throughout development. In the mesencephalic region, nNOS immunoreactivity was seen in the optic tectum, torus longitudinalis, nucleus of median longitudinal fascicle and occulomotor nucleus indicate the role of NO in integration of visual inputs and modulates motor control of the eyes and movements. Caudally, in the rhombencephalon, the cerebellum, the nucleus reticularis, the octaval nucleus and the motor nucleus of vagal nerve were nNOS positive during development. nNOS reactive cells and fibers were noted in the spinal motor column, thus suggesting a role of NO in gestation and startle response from early development.